Kewenangan Penyidik Menetapkan Rehabilitasi Tanpa Penetapan Pengadilan pada Kasus Penyalahgunaan Narkotika - Reza Setyawan; Anton Hendrik Samudra (Fakultas Hukum Universitas Surabaya, 2019)
This article reviews criminal justice process in deterring drug abuse case, discussing rehabilitation as a part of criminal sanction and the implementation or existence without court ruling or decision. Several rules and regulations discussed in resolving this matter include Law Number 35 of 2009 concerning Narcotics and Government Regulation Number 25 of 2011 concerning Mandatory Implementation of Narcotics Addict Report. The article was a part of bachelor’s degree thesis, conducted using normative legal study with case approach method. The case discussed is about rehabilitation of drug abuser Without Court’s order. The research finding is investigator do not have authority to place the drug abuser under rehabilitation. It is supposedly by court’s order.